Pelatihan dan Pembekalan Digital Marketing melalui Media Sosial sebagai upaya Peningkatan Penjualan pada UMKM Sumotea Salatiga - Rahardjo, Yohanes Dandyanto; Lays, Amelia Angelica; Saputri, Savera Apriliana; Ammar, Syahrul; Sulistyaningsih, Erna; Sugiarto, Agus (Empowerment, 2024)
The rapid advances in technology in this day and age require that people understand how to utilize and use technology optimally and well.  Digital marketing can make it easier for people to market their business.  One of the digital marketing platforms that is often used is social media.  The use of search engine optimization and the use of social media are some forms of digital marketing activities that are popular today.  Social media has different characteristics and can be adapted to the needs of business people.  Moreover, currently jumbo ice products are going viral and are increasingly in demand by the public.  This will open up opportunities for Sumotea MSMEs on Jalan Jagersari Argomulyo Salatiga to be given understanding and instruction in appropriate digital marketing strategies and good use of social media in order to expand their market reach, by utilizing social media such as Instagram, TikTok, Websites and others.  other.